Hypoxia-inducible Vascular Endothelial Growth Factor-engineered Mesenchymal Stem Cells Prevent Myocardial Ischemic Injury - Kim, Sun Hwa (Nature Publishing Group, 2011)
In the absence of repair mechanisms involving angiogenesis and cardiomyogenesis, loss of cardiomyocytes after myocardial injury is a primary causative factor in the progression toward heart failure. In an effort to reduce ischemic myocardial damage, we investigated the effects on infarcted myocardium of transplantation of genetically modified mesenchymal stem cells (MSCs) that specifically expressed vascular endothelial growth factor (VEGF) under hypoxic conditions. A hypoxia-inducible VEGF expression vector was introduced into MSCs (HI-VEGF-MSCs) using a nonviral delivery method, which were then used for the treatment of ischemic myocardial injury in rats. In HI-VEGF-MSCs, VEGF expression was significantly increased by hypoxia in vitro as compared to normoxia. Likewise, in vivo administration of HI-VEGF-MSCs induced ischemia-responsive VEGF production, leading to a significant increase in myocardial neovascularization after myocardial infarction. When compared with unmodified-MSCs, HI-VEGF-MSCs were retained in infarcted myocardium in greater numbers and remarkably reduced the number of apoptotic cells the infarcted area. Transplantation of HI-VEGF-MSCs resulted in a substantial attenuation of left ventricular remodeling in rat myocardial infarction. This study demonstrates that cell-based gene therapy using genetically engineered MSCs to express VEGF in response to hypoxic stress can be a promising therapeutic strategy for the treatment of ischemic heart disease.